What Do We Talk About Now When We Talk About Segmentectomy for GGO? - Li, Hanyue; Shen, Chen; Chen, Yang; Wang, Yiyang; Zhong, Chenxi; Fang, Wentao (Frontiers in Surgery, 2022)
Segmentectomy has been considered as a compromised procedure in early-stage lung cancer patients who could not tolerate a standard lobectomy. With the use of computed tomography (CT) screening, lung cancers are increasingly detected at earlier stages, especially those appearing as ground glass opacity (GGO)-containing lesions on CT scan. This has led to the revival of segmentectomy as an intentional procedure with the aim to cure in selected patients, as GGO-containing lesions represent a special group of diseases that are relatively indolent in nature and seldom have lymphatic involvement. Limited resections, especially anatomical segmentectomy, may thus be helpful in reducing peri-operative risks and preserving more pulmonary function for the patients, while retaining similar oncological outcomes. However, clinical trials focusing specifically on the role of segmentectomy in the treatment of GGO-containing lung cancers are still lacking, especially in the minimally invasive surgery setting. Emerging evidences suggest that for such lesions, the oncological non-inferiority of segmentectomy to standard lobectomy may not be limited to lesions sized ≤2cm. More importantly, it is still unclear whether segmentectomy would indeed minimize peri-operative risks and to what extent it could help preserve more pulmonary function in good-risk patients with a lesser extent of lung parenchyma resection. Hence, it is critical to re-evaluate the efficacies of minimally invasive segmentectomy including not only the oncological outcomes but also peri-operative results and pulmonary function changes compared with lobectomy in good-risk patients with GGO-containing lung cancers. All these remain to be explored in future studies and robust evidences are still in need to prove that patients would indeed benefit from the combination of segmentectomy together with minimally invasive surgery.